2018
DOI: 10.2196/11350
|View full text |Cite
|
Sign up to set email alerts
|

Dual Use of a Patient Portal and Clinical Video Telehealth by Veterans with Mental Health Diagnoses: Retrospective, Cross-Sectional Analysis

Abstract: BackgroundAccess to mental health care is challenging. The Veterans Health Administration (VHA) has been addressing these challenges through technological innovations including the implementation of Clinical Video Telehealth, two-way interactive and synchronous videoconferencing between a provider and a patient, and an electronic patient portal and personal health record, My HealtheVet.ObjectiveThis study aimed to describe early adoption and use of My HealtheVet and Clinical Video Telehealth among VHA users wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 17 publications
1
75
0
Order By: Relevance
“…Care providers’ role differs from that of general online facilitators in online meetings, in that they manage multilateral communication between patients and specialists and although there is a designated telehealth platform for their communications, sometimes, communication with the two different groups involves the use of additional technologies that complement or substitute the existing technology’s capabilities. Given that providers [58] and patients [90] were the main user groups of interest in previous studies for predicting telehealth technologies’ success, this study contributes to the health care literature by examining the adaptive structuration theory of individual from a care provider’s perspective and identifying salient constructs (the exploitative use of IT) in a research model to develop a contextualized theory. Second, the result that habit plays a significant role in adaptive IT use calls for more attention in IS research on how users’ habits accumulate from different life domains to affect their postadoptive use of multiple technologies [91].…”
Section: Discussionmentioning
confidence: 99%
“…Care providers’ role differs from that of general online facilitators in online meetings, in that they manage multilateral communication between patients and specialists and although there is a designated telehealth platform for their communications, sometimes, communication with the two different groups involves the use of additional technologies that complement or substitute the existing technology’s capabilities. Given that providers [58] and patients [90] were the main user groups of interest in previous studies for predicting telehealth technologies’ success, this study contributes to the health care literature by examining the adaptive structuration theory of individual from a care provider’s perspective and identifying salient constructs (the exploitative use of IT) in a research model to develop a contextualized theory. Second, the result that habit plays a significant role in adaptive IT use calls for more attention in IS research on how users’ habits accumulate from different life domains to affect their postadoptive use of multiple technologies [91].…”
Section: Discussionmentioning
confidence: 99%
“…This type of PHR is called by many different names, such as EHR-tethered PHR portal, tethered PHR portal, PHR portal, or simply, patient portal. One example of a PHR portal is My HealtheVet from the Veterans Health Administration [10,11]. Another example is MyChart , created by Epic Systems Corporation and used by many hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Involvement and feedback that reflects the diversity of the community can allow organizations to gain a better understanding of the diversity in patient needs [59,68,76,77]. Studies suggested that there were economic and ethnic disparities associated with the use and adoption of health IT [78,79]. Future studies could explore methods in which current engagement strategies can be adapted to effectively engage patients and families from underserved populations.…”
Section: Discussionmentioning
confidence: 99%